Pridobitve in ovire prenovljenih učnih načrtov v gimnaziji - Ivanuš-Grmek, Milena (Šolsko polje, 2010)
The introduction contains some relevant fi ndings in curricular theory concerning the upgrading of syllabus contents. Th e major part of the paper presents the results of our research, carried out with the purpose of pointingout both the benefi ts and the drawbacks of the implementation of curriculum renewal in grammar school education. Th e processing of data about selected characteristics of syllabus contents led to important fi ndings aboutthe benefi ts as well as the problems encountered by grammar school teachers in their pedagogical practice.
Keywords: curriculum renewal; gimnazija; grammar school; introduction of renewed syllabus contents; posodabljanje učnih načrtov; uvajanje; vzgoja in izobraževanje